A system-level method for hardening phase-locked loop to single-event effects - Bin Liang; Xinyu Xu; Hengzhou Yuan; Jianjun Chen; Deng Luo; Yaqing Chi; Hanhan Sun (Materials Research Express, 2022)
To mitigate the sensitivity of the charge pump in a traditional Phase-Locked Loop(PLL), a single-event-hardened PLL architecture with a proportional and integral path is proposed. The phase margin of the PLL is kept at 58.16° due to the rational design and the output clock frequency ranges from 0.8 to 3.2 GHz. The circuit-level simulation results reveal that the sensitive volume of the hardened PLL decreases by 80% ∼ 95%. The novel radiation-hardened PLL circuit was implemented in a 28 nm CMOS technology and irradiated with heavy ions with a linear energy transfer between 1.9 and 65.6 MeV•cm ^2 mg ^−1 . The proposed radiation-hardened PLL shows one order of single-event effects hardness level higher than the conventional PLL.